La identidad nacional ecuatoriana entre límites externos y internos - Chiara Pagnotta (Les Cahiers ALHIM)
In this article I mean to focus on the birth of the Ecuadorian nation, understood as a process of distinction and creation of external and internal boundaries with regard to the imagined national community. Once independence has been gained, the demarcation of national borders becomes the fundamental means through which the new state exercises sovereignty on a territory recognized as its own. In the Ecuadorian process of national identity building, history undertakes the task of regulating (collective) memory and oblivion in order to value the community’s distinctive traits and to differentiate it from other nations, specifically from Peru. In other words, history is manipulated to create a representation of the past aimed at ruling over the present. For what concerns the establishment of internal boundaries, it is important to draw attention on the development of a conception of Ecuador as a mestizo nation, that reached its peak in the populist period. This ideology perceives socio-cultural diversities as the legacy of an uncompleted process of nation-state building, meant to be overcome by the mestizaje.